Study on different concentrations and timings of 17α-methyltestosterone to accumulate in water flea (Moina spp.) from lab-scale - Pilapang, K.; Dandrit, D.; Yomla, R. (International Journal of Agricultural Technology, 2022)
The different concentrations and immersion times of 17α-methyltestosterone (17MT) on the accumulation in water flea were investigated. Results were found that amount of 17MT of both groups in each period displayed significantly different (P <0.05) when compared to the control. The highest accumulation of 17MT was found at the concentration of 100 mg / L for 420 minutes equal to 0.46 ± 0.10 mg/L. In contrast, it was found that the amount of 17MT in both concentrations of water at three times was not statistically significant (P> 0.05)in each treatment. Therefore, results indicated that the accumulation of 17MT in water fleas can be applied for using accumulated water flea to produce male tilapia